Analisis Permeabilitas Tanah pada Tubuh Waduk Gedang Kulut - Mochammad Dias Eca Mantofani; Edy Priyanto; Dandy Nugroho (Jurnal Kridatama Sains dan Teknologi, 2026)
Soil permeability is one of the key geotechnical parameters that describes the ability of soil to transmit water through its pore spaces. In reservoir construction, soil permeability significantly influences seepage, which may affect water storage efficiency and the stability of the reservoir embankment. This study aimed to determine the soil permeability coefficient of the Gedang Kulut Reservoir embankment and to analyze its permeability characteristics as a parameter for evaluating the suitability of the embankment material. A quantitative method with a descriptive-analytical approach was employed. Undisturbed soil samples were collected from a single sampling point, followed by five permeability tests using the Constant Head Test method based on Darcy’s Law. In addition, particle-size distribution analysis was conducted using sieve analysis to support soil characterization. The results showed that the permeability coefficients obtained from the five tests were 0.00043, 0.00034, 0.00025, 0.00039, and 0.00031 cm/s, respectively, with an average value of 0.000344 cm/s (3.44 × 10⁻⁶ m/s). Based on the soil permeability classification, the soil was categorized as having low permeability, indicating a relatively low capacity to transmit water. These findings suggest that, in terms of permeability, the soil at the study site is suitable for use as embankment material for the reservoir. Nevertheless, a comprehensive evaluation of material suitability requires further assessment of other geotechnical parameters